ANALISIS VARIASI JARAK PEMBULUH TERHADAP UNJUK KERJA KONDENSOR - Komala Dewi, AAIAS; Sukadana, IGK (Jurnal Energi Dan Manufaktur; Vol 2, No.2 Desember 2007, 2012)
The serpentine tube heat exchanger is one of most widely used heat exchanger to release heat by natural convection. The ability of the tube heat exchangerto release the heat is represented by its efficiency. The present research analyzed the effect of space between tubes and the mass flow rate to the tube heat exchanger efficiency. Three serpentine tube spaces (4 cm, 5 cm, and 6 cm, respectively), and three mass flow rates (0.015 kg/s, 0.018 kg/s, and 0.021 kg/s, respectively) were varied experimentally. The result showed that the highest efficiency was reached with mass flow rate 0.021 kg/s and space between tubes 5 cm.
Keywords: Efficiency, heat exchanger, natural convection